2009
DOI: 10.1093/schbul/sbp068
|View full text |Cite
|
Sign up to set email alerts
|

When Top-Down Meets Bottom-Up: Auditory Training Enhances Verbal Memory in Schizophrenia

Abstract: A critical research priority for our field is to develop treatments that enhance cognitive functioning in schizophrenia and thereby attenuate the functional losses associated with the illness. In this article, we describe such a treatment method that is grounded in emerging research on the widespread sensory processing impairments of schizophrenia, as described elsewhere in this special issue. We first present the rationale for this treatment approach, which consists of cognitive training exercises that make u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 68 publications
7
123
1
8
Order By: Relevance
“…The other study concluded there were no gains in neurocognition and no changes in electroencephalogram (EEG) measures following 40 hours of BrainFitness training [36]. Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up.…”
Section: Neuroplasticity-based Approachesmentioning
confidence: 97%
“…The other study concluded there were no gains in neurocognition and no changes in electroencephalogram (EEG) measures following 40 hours of BrainFitness training [36]. Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up.…”
Section: Neuroplasticity-based Approachesmentioning
confidence: 97%
“…More importantly, they demonstrated that these basic improvements were associated with improvements in higher order functions, including linguistic processing, verbal cognition, and general cognition and that these changes were durable six months after training had concluded. 77) Similarly, a social cognition training regimen that included practice in the basic skill of emotion perception was demonstrated to improve not only social cognition, but also social functioning in patients with schizophrenia, suggesting that the benefits generalize from test performance to actual functioning. 80) Cognitive therapies, therefore, must both recognize and address the perceptual processing impairments that are present in schizophrenia if maximal improvements in higher order cognitive func-tions are to be achieved.…”
Section: )mentioning
confidence: 97%
“…Because deficits in simple perception necessitate an increased attentional load and recruitment of top-down operations to achieve basic processing, 77) fewer top-down resources are available for higher-level cognitive operations. 78) Given this connection, there is increasing emphasis on the idea that training targeting basic sensory processes and simple cognitive functions will ultimately benefit higher-level cognitive operations.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it appears questionable if the modulation of a particular symptom embedded in a system of various disordered components leads to a recovery from the full range of deficits. Sensory processing and higher order cognitive performance display mutual dependence: perception contributes significantly to proper cognition (bottom-up) and cognition, in turn, modulates perception (top-down) (Javitt, 2009;Adcock et al, 2009). Thus, framing a valid hypothesis regarding schizophrenia by assuming a close relationship between phenomenology and neurophysiology appears critical.…”
Section: Third Approach: Modulation Of Neural Oscillationsmentioning
confidence: 99%